Pengaruh Fraksi Volume Dan Panjang Serat Pelepah Lontar (Borassus Flabellifer) Terhadap Kekuatan Tarik Dan Kekuatan Impak Komposit Bermatrik Epoksi - Tuati, Amros Alfonsius; Purnowidodo, Anindito; Sonief, Achmad As’ad (Jurnal Rekayasa Mesin, 2015)
This study was conducted using epoxy resin as ligature and midrib lontar fibers (borassus flabellifer) as brace. Composite was made by varied fiber volume fraction 10%, 30% and 50% with length variation 10 mm, 20 mm, and 30 mm. The composite production used hand lay-up method. The test result showed the highest composite tensile strength about 31.607 Mpa in volume fraction 10% with fiber length 30 mm. The lowest composite tensile strength was about 16.855 Mpa in fiber volume fraction 10% and 20 mm in fiber length. Moreover, the highest composite impact strength was 0.00163 J/mm in fiber volume fraction 50% with fiber length 30 mm and the lowest impact strength was 0.00214 J/mm 2 in fiber volume fraction 10% and 10 mm fiber length. The kind of composite fracture tended to have brittle fracture with mechanism of fiber pull out.